First comprehensive proteome analysis of lysine crotonylation in seedling leaves of Nicotiana tabacum - Hangjun Sun (Nature Portfolio, 2017)
Abstract Histone crotonylation is a new lysine acylation type of post-translational modification (PTM) enriched at active gene promoters and potential enhancers in yeast and mammalian cells. However, lysine crotonylation in nonhistone proteins and plant cells has not yet been studied. In the present study, we performed a global crotonylation proteome analysis of Nicotiana tabacum (tobacco) using high-resolution LC-MS/MS coupled with highly sensitive immune-affinity purification. A total of 2044 lysine modification sites distributed on 637 proteins were identified, representing the most abundant lysine acylation proteome reported in the plant kingdom. Similar to lysine acetylation and succinylation in plants, lysine crotonylation was related to multiple metabolism pathways, such as carbon metabolism, the citrate cycle, glycolysis, and the biosynthesis of amino acids. Importantly, 72 proteins participated in multiple processes of photosynthesis, and most of the enzymes involved in chlorophyll synthesis were modified through crotonylation. Numerous crotonylated proteins were implicated in the biosynthesis, folding, and degradation of proteins through the ubiquitin-proteasome system. Several crotonylated proteins related to chromatin organization are also discussed here. These data represent the first report of a global crotonylation proteome and provide a promising starting point for further functional research of crotonylation in nonhistone proteins.